The Influence of Halal Labels and Production Material Quality on Consumer Purchasing Decisions at Mochi Chuwi MSMEs in Tebing Tinggi City - S, Azra Afwani; Jannah, Nurul; Bi Rahmani, Nur Ahmadi (Universitas Ibn Khladun Bogor, 2025)
The purpose of this study is to evaluate and assess the impact of Halal Label on purchasing decisions, and the impact of the quality of production materials on purchasing decisions of Mochi produced by UMKM Mochi Chuwi Lingkungan III, Karya Jaya Village, Tebing Tinggi City, using a case study of the Tebing Tinggi City community. Quantitative techniques are applied in this study. The population in this study consists of the people of Tebing Tinggi City who usually shop at UMKM Mochi Chuwi Lingkungan III, Karya Jaya Village, Tebing Tinggi City, totaling 133 buyers per day, using the Slovin formula, a sample of 100 people was taken. In this study, data was collected through the use of questionnaires. Normality tests, validity tests, reliability tests, multiple regression tests, hypothesis tests (t-test and F-test), and coefficients of determination were all used in the data analysis approach of this study, which also included a literature review. Halal labels have a major impact on purchasing decisions. The quality of product materials has a major impact on purchasing decisions. Halal labels and the quality of production materials both have a major impact on purchasing decisions of Mochi produced by UMKM Mochi Chuwi Lingkungan III, Karya Jaya Village, Tebing Tinggi City.